Apseudes talpa revisited (Crustacea; Tanaidacea).The impact on apseudidaen systematics - Larsen, Kim; Bertocci, Iacopo; Froufe, Elsa (Zootaxa, 2011)
The species Apseudes talpa is redescribed and its impact on the systematics of Apseudidae is discussed. The finding of multiple conflicting characters with the generic diagnosis, as well as the novel character of a denticulate ridge on the mandibular body, suggest that a redefinition of the genus Apseudes is necessary. The genus Androgynella is here demoted to a junior synonym of Apseudes.